Antioxidant status in elite three-day event horses during competition - Williams, C. A.; Burk, A. O. (Canadian Respiratory Journal, 2012)
The objective of this study was to determine if competition intensity would have an effect on antioxidant status in horses before and during a three-day event. Body weight, body condition score, and blood was sampled from CCI2* (n = 19) and CCI3* (n = 23) horses before the start of dressage, 20 to 30 min following cross-country, and 18-24 h after cross-county. Data were analyzed using a PROC MIXED in SAS. There were no differences between CCI2* and CCI3* horses during competition for plasma cortisol, lactate, -tocopherol, retinol, or erythrocyte glutathione peroxidase. After cross-country, CCI3* horses had higher serum creatine kinase (P = 0.003) and aspartate aminotransferase (P < 0.001) than the CCI2* horses. Plasma -carotene was higher in the CCI2* horses compared to the CCI3* horses (P = 0.001). Total erythrocyte glutathione was also higher in the CCI2* horses versus CCI3* horses (P < 0.001). These results are the first report of antioxidant status of horses competing in this level of a three-day event. The changes in antioxidant and muscle enzymes observed between divisions are likely due to the increased anaerobic and musculoskeletal demand on the upper level horses and the fitness required to compete at that level.